FISIOLOGI PASCA PANEN PADA BUNGA ANGGREK POTONG - -, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2007)
ABSTRACT Orchids are plants that have many types of both types of flowers or kind. The orchid lovers cultivate a collection to enjoy its beauty or cultivated as cut orchid. As cut orchid, flowers have long durability, yet efforts to maintain the freshness of the flowers still needed. One way to keep your look fresh flowers are still beautiful and with proper post-harvest handling.The main factor is the interest rate the quality effect aging, temperature, water supply, food and mechanical damage. Cheapest techniques to maintain freshness after the cut orchid flowers is by way of the base of the flower stalk that has been wrapped with cotton didibasahi with sugar-sweetened water and then put a plastic bag on the belt. Key word : Handling cut flowers orchid